2021
DOI: 10.1155/2021/1894155
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility of Dapagliflozin and Empagliflozin in a Real-World Heart Failure Population

Abstract: Aims. This study is aimed at investigating the eligibility in a real-world heart failure population for the DAPA-HF (testing dapagliflozin) and EMPEROR-reduced (testing empagliflozin) trials, comparing the eligible real-world patients to trial participants and to characterize the noneligible patients. Methods. Medical records of all heart failure patients who had a diagnosis of heart failure from the Heart Centre or Department of Internal Medicine at Umeå University Hospital were reviewed. Results. 2433 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…4,27 However, our study showed that these criteria also led to the exclusion of half and one-quarter of patients, respectively, limiting eligibility. Accordingly, our estimated eligibility for vericiguat was mostly lower than previous eligibility estimates for other HF therapies, such as sodium-glucose cotransporter 2 inhibitors (trial eligibility: 39-52% [28][29][30][31] ; label eligibility: 86% 30 ) and sacubitril/valsartan (trial eligibility: 24-38% [32][33][34][35][36] ; label eligibility: 84% 35 ), but higher than ivabradine (trial eligibility: 14%). 37 These findings highlight the difficulties in balancing enrichment strategies against feasibility of enrolment when designing trials.…”
Section: Eligibility According To the Trial Guideline And Label Scena...contrasting
confidence: 71%
“…4,27 However, our study showed that these criteria also led to the exclusion of half and one-quarter of patients, respectively, limiting eligibility. Accordingly, our estimated eligibility for vericiguat was mostly lower than previous eligibility estimates for other HF therapies, such as sodium-glucose cotransporter 2 inhibitors (trial eligibility: 39-52% [28][29][30][31] ; label eligibility: 86% 30 ) and sacubitril/valsartan (trial eligibility: 24-38% [32][33][34][35][36] ; label eligibility: 84% 35 ), but higher than ivabradine (trial eligibility: 14%). 37 These findings highlight the difficulties in balancing enrichment strategies against feasibility of enrolment when designing trials.…”
Section: Eligibility According To the Trial Guideline And Label Scena...contrasting
confidence: 71%
“…In the RICA registry, which included patients aged ≥50 years admitted with HF to internal medicine departments in Spain between 2008 and 2019, the mean age was 80 years, up to a third of patients were in functional class III, more than 60% had HFpEF, and comorbidity was very common [ 17 ]. Various studies have indicated that in clinical practice, a high number of patients with HF would be eligible for treatment with SGLT2i [ 18 , 19 ]. In fact, in a recent study that analyzed the eligibility of the four pharmacologic pillars for treatment of HFrEF at discharge from hospital, SGLT2i were more frequently prescribed than RAAS inhibitors and mineralocorticoid receptor antagonists, with kidney failure being the main factor limiting prescription of these agents, in contrast with SGLT2i [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence from clinical trials and sub-studies has demonstrated that dapagliflozin reduces not only HF (re-)hospitalizations, but also cardiovascular mortality (NNT = 68) and all-cause death (NNT = 67) in the whole spectrum of HF, without a loss of efficacy according to ejection fraction [92]. On the other hand, different studies have shown that a great proportion of patients with HF in clinical practice are eligible for dapagliflozin according to the DAPA-HF and DELIVER criteria [102][103][104][105][106][107][108]. In addition, the full implementation of dapagliflozin in real-life populations would prevent/postpone new worsening HF events or even death [102,[106][107][108].…”
Section: Discussionmentioning
confidence: 99%